On the enigmatic origin of the Mediterranean invasive Caulerpa racemosa (Caulerpales, Chlorophyta) - PANAYOTIDIS, P. (Mediterranean Marine Science, 2006)
The successful sexual reproduction of the Mediterranean invasive species Caulerpa racemosa could explain not only its rapid expansion during the last decade of the 20th century, but also its origin, through hybridation and genetic recombination of preexisting varieties. This paper argues on the cryptogenic origin of the Mediterranean invasive Caulerpa racemosa.